Juridical Review of Dispute Resolution Between Manulife Life Insurance Indonesia vs Derama Laia: (Studi Putusan Nomor 1867K/Pdt.Sus-BPSK/2022) - Khoirunnisa, Alfiatun; Lesmana, Sri Jaya; Ratna Indayatun (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2025)
This study aims to review juridically the settlement of consumer protection disputes between PT Asuransi Jiwa Manulife Indonesia and Derama Laia from the perspective of civil law. This case began with a dispute related to the implementation of the insurance agreement regulated in the policy between the two parties. The dispute was then brought before the Consumer Dispute Settlement Agency (BPSK) and decided through Supreme Court Decision Number 1867 K/Pdt.Sus-BPSK/2022, which stated that this case was more of a contractual dispute than a violation of consumer protection. Through a normative approach, this study analyzes the conformity of the decision with Law Number 8 of 1999 concerning Consumer Protection and the Civil Code (KUH Perdata). The results of the study show that the dispute resolution should be through civil law because it concerns the fulfillment of the agreement between the two parties, not a matter of consumer protection. This study recommends that disputes related to the performance of contracts should be directed to the Civil Court or Arbitration to avoid jurisdictional confusion and ensure proper settlement in accordance with applicable law.